2020
DOI: 10.7554/elife.56384
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural comparison of dendritic spine morphology preserved with cryo and chemical fixation

Abstract: Previously we showed that cryo fixation of adult mouse brain tissue gave a truer representation of brain ultrastructure in comparison with a standard chemical fixation method (Korogod et al 2005). Extracellular space matched physiological measurements, there were larger numbers of docked vesicles and less glial coverage of synapses and blood capillaries. Here, using the same preservation approaches we compared the morphology of dendritic spines. We show that the length of the spine and the volume of its head i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…Previous studies in living tissue have reported no correlation between spine head and neck parameters (Araya et al, 2014;Tønnesen et al, 2014). Studies in fixed tissue have found weak correlations between head volume and neck diameter in chemically fixed spines, but not in cryo-fixed spines (Arellano et al, 2007;Bartol et al, 2015;Tamada et al, 2020). We used our dataset and analysis pipeline to explore this issue with a larger number of ultrastructural reconstructed spines (Figure 5).…”
Section: Correlations Between Spine Morphological Parametersmentioning
confidence: 99%
“…Previous studies in living tissue have reported no correlation between spine head and neck parameters (Araya et al, 2014;Tønnesen et al, 2014). Studies in fixed tissue have found weak correlations between head volume and neck diameter in chemically fixed spines, but not in cryo-fixed spines (Arellano et al, 2007;Bartol et al, 2015;Tamada et al, 2020). We used our dataset and analysis pipeline to explore this issue with a larger number of ultrastructural reconstructed spines (Figure 5).…”
Section: Correlations Between Spine Morphological Parametersmentioning
confidence: 99%
“…The key element in dendritic spine staining is to apply an appropriate, gentle tissue fixation to assess the relevant effects on spine structure and eliminate cascades of biochemical processes affecting biophysical properties of neuronal membrane caused by cell death [ 32 , 96 , 98 , 99 ], therefore the vital condition of cells is an important factor in accurate spine analysis [ 97 , 100 ]. It is still not clear how in vitro, ex vivo, and in vivo models differ in speed of biochemical processes [ 97 , 100 , 101 , 102 ]. Therefore, the live cell imaging approach constitutes a suitable alternative, however, it requires analyzing more neurons, culture or animals per group due to technical limitations during live imaging.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Investigation of all the parameters including neck width is achievable also using serial section electron microscopy (EM), which enables a detailed morphometric analysis at the nanoscale [ 127 , 128 , 129 ]. However, in the EM imaging, a sample needs to be fixated, permeabilized, dehydrated, and also placed under high vacuum—these procedures include the type of sample fixation (cryo- or chemical- fixation) that frequently causes structural artifacts to disturb the morphometric parameters of the dendritic spines [ 101 , 130 , 131 ] (comparative morphological analysis of images from live imaging and their respective images obtained using EM, see [ 130 , 131 ]). Currently, the most popular method used for precise dendritic spines imaging is based on super-resolution fluorescent light microscopy (lateral resolution around 20 to 40 nm in fixed tissue) through an expression of fluorescent membrane proteins that reduce an impact of sample preparation [ 101 , 132 ].…”
Section: Experimental Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrastructure of neurons also varies depending on the choice of fixative. Compared with rapid cryofixation of tissue, aldehyde-based chemical fixatives greatly reduce the space occupied by the extracellular matrix and increase the spine neck width (Korogod et al, 2015 ; Tamada et al, 2020 ). Therefore, great care should be taken in interpreting EM data and special caution should be applied when comparing data obtained from using different fixation conditions.…”
Section: Technical Considerations and Limitations Of Volume Em Studiesmentioning
confidence: 99%